Arthroscopically Assisted Acromioclavicular Joint Reconstruction With 2.0-mm Tunnel in the Clavicle and Suture Looping Around the Coracoid Process - Peiguan Huang, M.Med.; Xiaoxu Wang, M.Med.; Yong Fu, M.D.; Zhengmao Li, M.D.; Bin Peng, M.Med.; Min He, M.Med.; Chunrong He, M.D. (Arthroscopy Techniques)
Arthroscopic acromioclavicular joint (ACJ) reconstruction is widely applied in ACJ dislocation. A 4.0-mm bone tunnel is the most used size in the clavicle; drilling a bone tunnel in the coracoid process is also commonly applied. However, large-diameter bone tunnels in the clavicle and coracoid process may cause many complications. Therefore, we present a pragmatic surgical technique of ACJ reconstruction with a 2.0-mm tunnel in the clavicle and looping the suture around the coracoid process. Due to the minimal trauma to the bone, the risk of fracture in the clavicle and the coracoid process can be significantly reduced; repeated drilling in the bone will not occur, and surgical difficulty and time will be greatly reduced accordingly.